Testicular pain as an unusual presentation of COVID-19: a brief review of SARS-CoV-2 and the testis. Issue 5 (November 2020) - La Marca, Antonio; Busani, Stefano; Donno, Valeria; Guaraldi, Giovanni; Ligabue, Guido; Girardis, Massimo
Abstract: Research question: Can the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus induce testis damage and dysfunction? Design: This is the description of the case of a young man presenting with heavy testicular pain as the first symptom of COVID-19 infection. A review of the literature is also presented. Results: SARS-CoV-2 may enter into the host cell by binding to angiotensin-converting enzyme 2. This receptor seems to be widely expressed in different testicular cell types, making possible the occurrence of orchitis in male patients with COVID-19 infection. From a review of the literature, it seems that there is currently no evidence of sexual transmission of SARS-CoV-2; however, the possibility of virus-induced testis damage and dysfunction cannot be excluded. Conclusions: Further studies are necessary on the pathological effect of SARS-CoV-2 in the male reproductive system and to ensure a proper andrological follow-up for male patients.